2019
DOI: 10.1051/metal/2019062
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hybrid reinforcement at stirred zone of dissimilar aluminium alloys during friction stir welding

Abstract: The main objective of this work is to modify the mechanical as well as surface properties of weld nugget by the reinforcement of hybrid ceramic particles (alumina and silicon carbide). This is accomplished by combining friction stir welding (FSW) and friction stir processing (FSP) on dissimilar AA6101-T6 and AA1350 aluminium alloys. For this purpose, various levels of mixing proportions of Al2O3 & SiC particles are used with constant groove depth and width i.e. constant groove dimension. To evaluate the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Compatible reinforcement particles inside of the groove/the isolation film might support the joint, since FSW studies on groove details and appropriate reinforcement material have already shown improvements in mechanical properties. 45,46…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compatible reinforcement particles inside of the groove/the isolation film might support the joint, since FSW studies on groove details and appropriate reinforcement material have already shown improvements in mechanical properties. 45,46…”
Section: Resultsmentioning
confidence: 99%
“…Compatible reinforcement particles inside of the groove/the isolation film might support the joint, since FSW studies on groove details and appropriate reinforcement material have already shown improvements in mechanical properties. 45,46 Besides the polymeric film, also the surface pretreatment has a relevant influence on the joint aging behavior. Goushegir et al 47 concluded that during accelerated aging of FSpJ joints the complete wetting of aluminium surface with molten polymer hinders the moisture diffusion into the joint interface.…”
Section: Effect Of Pps Interlayermentioning
confidence: 99%
“…Due to the possibility of influencing heat production during the material joining process, it is conceivable that the FSW tool will not affect weld quality. 10,11 In this work, the FSW tool was successfully fabricated with required dimensions by using Computer Numerical Control (CNC) machine and checking the dimensions were used profile projector and check wear loss of the tool pin via the optical microscope image. The tool material used in this experiment has a high carbon and a high chromium content tool steel (HCHCR).…”
Section: Methodsmentioning
confidence: 99%
“…Better mechanical properties and wear resistance were obtained in FSWed joint of AA6101 and AA1350 incorporated with Al 2 O 3 than that of incorporated with SiC. 17 Reinforcing of TiO 2 nanoparticles in the weld joint of AA6063-T4 and AZ31-O magnesium alloy augmented the tensile strength almost two times higher on comparing without reinforced welded joint. 18…”
Section: Introductionmentioning
confidence: 90%